Ecology, Planning, and Management of Urban Forests International Perspective - Carreiro, Margaret M.; Carreiro, Margaret M.; Song, Yong-Chang.; Song, Yong-Chang.; Wu, Jianguo.; Wu, Jianguo. (Springer Series on Environmental Management, 2008)
Urban forests play a fundamentally important role in building ecological cities. They improve the environmental quality of the urban environment and the aesthetics of urban landscapes, and in many developed and developing countries, the evolution of urban forestry has been recognized as an essential means of maintaining urban ecosystem health, improving human living conditions, fostering a harmonious human-nature relationship, and ultimately achieving urban sustainability. Ecology, Planning, and Management of Urban Forests contains studies and perspectives on urban forests from a broad array of basic and applied scientific disciplines including ecosystem ecology, biogeochemistry, landscape ecology, plant community ecology, geography, and social science. The book contains contributions from experts in Asia, Europe, and North America, allowing the reader to evaluate methods and management that are appropriate for particular geographic, environmental, and socio-political contexts. Urban forests are also approached on regional and landscape scales to encompass more natural environments in and around cities, rather than within arbitrary municipal boundaries. The studies provided are intended to motivate scientists, planners, and managers to work together and to adopt a broader landscape ecology approach to urban forestry, and in so doing, better address the pressing needs for improving the quality of life in urban environments. About the Editors: Dr. Margaret M. Carreiro is Associate Professor in the Biology Department of the University of Louisville, Louisville, Kentucky, USA. Dr. Yong-Chang Song is Professor in the Department of Environmental Sciences at East China Normal University, Shanghai, China. Dr. Jianguo Wu is Professor of Ecology and Sustainability Science in the School of Life Sciences and Global Institute of Sustainability at Arizona State University, Tempe, Arizona, USA.